1996
DOI: 10.1074/jbc.271.2.611
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian AMP-activated Protein Kinase Subfamily

Abstract: The mammalian 5-AMP-activated protein kinase (AMPK) is related to a growing family of protein kinases in yeast and plants that are regulated by nutritional stress. We find the most prominent expressed form of the hepatic AMPK catalytic subunit (␣ 1 ) is distinct from the previously cloned kinase subunit (␣ 2 ). The ␣ 1 (548 residues) and ␣ 2 (552 residues) isoforms have 90% amino acid sequence identity within the catalytic core but only 61% identity elsewhere. The tissue distribution of the AMPK activity most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
551
1
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(572 citation statements)
references
References 25 publications
11
551
1
9
Order By: Relevance
“…Similarly, metformin, a widely used insulin sensitizer, has also very recently been shown to activate AMPK and to suppress gluconeogenesis in isolated liver cells [73], and could thus also inhibit insulin secretion directly. However, it should be stressed that the expression of AMPK catalytic subunit isoforms is different in β-cells (α1 α2) [10] than in muscle (α1 α2) [12] or liver cells (α1 $ α2) [29]. Given the existence of other possible differences in the relative abundances of the β-and γ-subtypes in these tissues, isoform-selective activators or inhibitors of AMPK may thus provide new therapeutic tools for the treatment of type 2 diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, metformin, a widely used insulin sensitizer, has also very recently been shown to activate AMPK and to suppress gluconeogenesis in isolated liver cells [73], and could thus also inhibit insulin secretion directly. However, it should be stressed that the expression of AMPK catalytic subunit isoforms is different in β-cells (α1 α2) [10] than in muscle (α1 α2) [12] or liver cells (α1 $ α2) [29]. Given the existence of other possible differences in the relative abundances of the β-and γ-subtypes in these tissues, isoform-selective activators or inhibitors of AMPK may thus provide new therapeutic tools for the treatment of type 2 diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have demonstrated that AMP-activated protein kinase (AMPK) is involved in the regulation of gene expression by glucose in this cell type [10]. AMPK is a multisubstrate, heterotrimeric serine\threonine protein kinase, consisting of a catalytic α-subunit and non-catalytic β-and γ-subunits [11,12]. Enzyme activity is regulated both allosterically by AMP, and through reversible phosphorylation at Thr-172 of the α subunit by an upstream kinase (AMPK kinase, or AMPKK) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…and SNF4 gene products, and is involved in yeast in the response to nutritional stress (starvation for glucose) [9][10][11][12]. A number of DNA sequences encoding proteins related to Snflp have been cloned from higher plants, including RKINI from rye [13], BKIN12 and BKIN2 from barley [14,15], AKINIO from A. thaliana [16], and NPK5 from tobacco [17].…”
Section: Introductionmentioning
confidence: 99%
“…Considered principally as an "emergency response" enzyme in mammals, activated only during severe metabolic stress during which intracellular 5'AMP levels were raised as those of ATP fell, AMPK was substantially ignored by all but a very few groups for the next twenty years (Stapleton et al, 1996;Hardie et al, 1998).…”
Section: Introductionmentioning
confidence: 99%